Human platelet lysate as a replacement for fetal bovine serum in human corneal stromal keratocyte and fibroblast culture - Seidelmann, Nina (2022)
The isolation and propagation of primary human corneal stromal keratocytes (CSK) are crucial for cellular research and corneal tissue engineering. However, this delicate cell type easily transforms into stromal fibroblasts (SF) and scar inducing myofibroblasts (Myo-SF). Current protocols mainly rely on xenogeneic fetal bovine serum (FBS). Human platelet lysate (hPL) could be a viable, potentially autologous, alternative. We found high cell survival with both supplements in CSK and SF. Cell numbers and Ki67+ ratios increased with higher fractions of hPL and FBS in CSK and SF. We detected a loss in CSK marker expression (Col8A2, ALDH3A1 and LUM) with increasing fractions of FBS and hPL in CSK and SF. The expression of the Myo-SF marker SMA increased with higher amounts of FBS but decreased with incremental hPL substitution in both cell types, implying an antifibrotic effect of hPL. Immunohistochemistry confirmed the RT-PCR findings. bFGF and HGF were only found in hPL and could be responsible for suppressing the Myo-SF conversion. Considering all findings, we propose 0.5% hPL as a suitable substitution in CSK culture, as this xeno-free component efficiently preserved CSK characteristics, with non-inferiority in terms of cell viability, cell number and proliferation in comparison to the established 0.5% FBS protocol.